Is the force-velocity profile for free jumping a sound basis for individualized jump training prescriptions? - Bobbert, M. F.; Lindberg, K.; Paulsen, G. (Medicine & Science in Sports & Exercise, 2025)
Introduction Formulating individualized optimized jump training prescriptions based on the force-velocity profile has become popular, but its effectiveness has been contested. Such training programs have opposite effects on "maximal average force" and "maximal average shortening velocity," and we set out to investigate which training-induced changes in the neuromuscular system could cause such effects.